2013
DOI: 10.4070/kcj.2013.43.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Ageing

Abstract: Arterial ageing is characterized by age associated degeneration and sclerosis of the media layer of the large arteries. However, besides ageing, clinical conditions, which enhance oxidative stress and inflammation act to accelerate the degree of arterial ageing. In this review, we summarized the pathophysiology and contributing factors that accelerate arterial ageing. Among them, we focused on hypertension, the renin-angiotensin-aldosterone system and vascular inflammation which are modifiable causes of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 55 publications
0
28
0
2
Order By: Relevance
“…Premature increase in arterial stiffness has been considered a risk factor for cardiovascular disease. The arterial stiffness of a subject increases with age, hypertension, and diabetes mellitus in addition to other factors (Lee and Park 2013). Different methods and devices are used to estimate arterial stiffness (Laurent et al 2006, Woodman et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Premature increase in arterial stiffness has been considered a risk factor for cardiovascular disease. The arterial stiffness of a subject increases with age, hypertension, and diabetes mellitus in addition to other factors (Lee and Park 2013). Different methods and devices are used to estimate arterial stiffness (Laurent et al 2006, Woodman et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…lifestyle and other effect modifiers) could have an effect on the penetrance of these alleles. Previous studies have shown that arterial stiffness is strongly influenced by factors such as age, blood pressure, dyslipidemia, diabetes, renal function and inflammation (14,15). The results from this study suggest that the main determinants of arterial stiffness are exogenous risk factors rather than genetic risk factors.…”
Section: Discussionmentioning
confidence: 54%
“…Second, it is noted that the arterial stiffness of a subject increase with age and cardiovascular disease. [13] Although the arterial stiffness is only one factor to cause the cardiovascular disease, we still should try to estimate the cardiovascular disease by the parameter associated with arterial stiffness in the future study, and compare the result with WI, which will help us to modify the WI for more accuracy and effect. …”
Section: Discussionmentioning
confidence: 99%